In vitro anticancer efficacy of a polyphenolic combination of Quercetin, Curcumin, and Berberine in triple negative breast cancer (TNBC) cells - Akanksha Kashyap; Sheikh Mohammad Umar; Arundhathi Dev J․R․; Mohini Mendiratta; Chandra Prakash Prasad (Elsevier, 2022)
Background: Among all breast cancers, Triple negative breast cancer (TNBC) is the most aggressive subtype with an increased metastatic and relapse rate. Presently, the only therapeutic option available for TNBC patients is standard chemotherapy. Past research on natural compounds has demonstrated their chemopreventive as well as therapeutic effects in various cancers. Compounds like quercetin (QUE), curcumin (CUR), and berberine (BBR) have been shown to induce pro-apoptotic, anti-proliferative, anti-migratory, and anti-metastatic effects in various cancers. Purpose: In the present study, we investigated the therapeutic potential of three natural compounds (QUE, CUR, and BBR) in the in vitro TNBC models. We also hypothesized that compared to their individual effects, combination treatment of all three polyphenols might enhance their in vitro efficacy in TNBCs. Methods: Using MDA-MB-468 and MDA-MB-231 as TNBC cell line models, we evaluated the effect of individual phytochemicals as well as their combined treatment (COMQUE+CUR+BBR) on Epithelial mesenchymal transition (EMT) statuses, migration potential, cancer stem cells (CSCs), clonogenic/3D matrigel growth capability and drug resistance in TNBC cells. Results: Our data demonstrated that the effect induced by the combination (COMQUE+CUR+BBR) treatment on EMT proteins and cell migration were significant and synergistic, compared with individual treatments. Additionally, COMQUE+CUR+BBR treatment significantly impaired the CD44+/CD24-population, clonogenic potential, and inherent cisplatin resistance in TNBC cells. For all our combination experiments, we have used 1/10thdose (to their respective IC50concentrations), thereby showing strong efficacy of these phytochemicals in TNBC models. Conclusion: These findings demonstrate for the first time that combination QUE, CUR, and BBR has potential in the treatment of TNBCs, owing to its anti-proliferative, EMT inhibitory, and antagonistic cancer stemness functions.